Polyurethane flexible foam recycling via glycolysis using Zn/Sn/Al hydrotalcites as heterogeneous catalyst (2018)
ABSTRACT : Polyurethane is a highly versatile material used in comfort, packaging and isolation industries. The global production of polyurethane generates several million tons of non-biodegradable wastes. In this research, the chemical recovery of polyol from polyurethane flexible foam (PUF) wastes was explored. The polyol recovery from PUF was carried out via glycolysis with diethylene glycol (DEG) as a glycolysis agent, Zn/Sn/Al hydrotalcite (HTC) as a heterogeneous catalyst under inert atmosphere using several reaction conditions. The most suitable reaction conditions were achieved for 3 h of reaction, PUF/DEG mass ratio of 1.5 and HTC/DEG of 0.001. The HTC was characterized by FTIR, XRD, TEM and chemical analysis. The recovered polyol was characterized using IR, viscometry and GPC; density and water content was also determined. The recovered polyol was used in the synthesis of PUF as a partial replacement of virgin polyols, and the resultant foams were analyzed using compression tests.